Analisis Quality of Service Pada Jaringan Komputer - Putra, Ida Bagus Agung Eka Mandala; Adnyana, Made Sri Indra Dewi; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P11, 2021)
The digital era where technological developments are growing rapidly, causing ease in accessing information from various parts of the world. The vast unlimited internet world can connect all computers throughout the world providing guidance in getting information, communicating and establishing partnerships. Computer networks are not new, it can be said that almost all organizations, agencies and digital agency companies use computer networks to support management activities. The need for computer networks is a top priority in organizations to be widely connected to facilitate access to information. With many computer network users in an organization / agency causing very heavy internet traffic. Therefore the importance of an administrator in the field of computer networks in bandwidth management. At Kesato Digital Agency, there are computer network problems when there is a dense internet traffic due to the unfair distribution of bandwidth to each user. Therefore it is necessary to assess the Quality of Service on the Digital Agency company's computer network. The results of the Quality of Service assessment on the Kesato Digital Agency in the satisfactory category, of course there needs to be efforts to improve to achieve maximum results in the very satisfying category.